2021
DOI: 10.1111/2041-210x.13646
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐fluorescence imaging and automated trophallaxis detection for studying multi‐nutrient regulation in superorganisms

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Overcoming this limitation will be facilitated by the ongoing development of techniques enabling the automated detection of specific social behaviours (e.g. trophallaxis [75,76]) and the study of their role in promoting or preventing disease spread [69].…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming this limitation will be facilitated by the ongoing development of techniques enabling the automated detection of specific social behaviours (e.g. trophallaxis [75,76]) and the study of their role in promoting or preventing disease spread [69].…”
Section: Discussionmentioning
confidence: 99%
“…Performance measurements (Table 1 ) showed that our trophallaxis detector outperforms the state of the art 8 , 24 . Its Matthews correlation coefficient (MCC) is 0.89, 0.28 higher than that of the best automatic honey bee trophallaxis detector so far 8 .…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Previously described automatic trophallaxis detectors are either unable to determine the direction of liquid transfer 8 , 9 , 23 or require fluorescence-labeled liquids and a more complex tracking system to do so 24 . To establish the liquid transfer direction directly from videos, we trained a second CNN (Supplementary Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trophallaxis is an efficient mechanism for the rapid transfer of nutrients among all colony members [24][25][26][27] . To date, food dyes 28,29 , radioactive-labeled food 24,26,[30][31][32][33] , and, recently, fluorescent-dyed food 34,35 , have been used to study the path of resources transferred via trophallaxis in hymenopterans. While these methods have provided valuable information on the food exchange dynamics within the colony, they are limited by the constraints of labeling the food resources as a whole.…”
mentioning
confidence: 99%